APPROPRIATE BINDER SELECTION TO APPLICATION REGION ACCORDING TO SUPERPAVE SYSTEM: BINGOL EXAMPLE - Ahmedzade, Perviz; Yilmaz, Mehmet; Geckil, Tacettin (Yildiz Technical Univ, 2007)
In this study, the weather temperature values that procured from Bingol Meteorology Nation Directorate were used to determine appropriate binder performance grade according to Superpave system. Dynamic Shear Rheometer (DSR) test was performed on the two types of binder (B 70/100 and B 100/150) obtained from TUPRAS refinery and was attempted to determine the appropriate binder in point of rutting resistance for Bingol. From obtained results, B 70/100 binder was found to be appropriate, but B100/150 binder to be not appropriate in point of rutting resistance at the regional weather conditions.
Keywords: Superpave; dynamic shear rheometer; rutting